Proteomics and bioinformatics analysis reveal potential roles of cadmium-binding proteins in cadmium tolerance and accumulation of Enterobacter cloacae - Chuanboon, Kitipong; Na Nakorn, Piyada; Pannengpetch, Supitcha; Laengsri, Vishuda; Nuchnoi, Pornlada; Isarankura-Na-Ayudhya, Chartchalerm; Isarankura-Na-Ayudhya, Patcharee (PeerJ, 2019)
Background Enterobacter cloacae (EC) is a Gram-negative bacterium that has been utilized extensively in biotechnological and environmental science applications, possibly because of its high capability for adapting itself and surviving in hazardous conditions. A search for the EC from agricultural and industrial areas that possesses high capability to tolerate and/or accumulate cadmium ions has been conducted in this study. Plausible mechanisms of cellular adaptations in the presence of toxic cadmium have also been proposed. Methods Nine strains of EC were isolated and subsequently identified by biochemical characterization and MALDI-Biotyper. Minimum inhibitory concentrations (MICs) against cadmium, zinc and copper ions were determined by agar dilution method. Growth tolerance against cadmium ions was spectrophotometrically monitored at 600 nm. Cadmium accumulation at both cellular and protein levels was investigated using atomic absorption spectrophotometer. Proteomics analysis by 2D-DIGE in conjunction with protein identification by QTOF-LC-MS/MS was used to study differentially expressed proteins between the tolerant and intolerant strains as consequences of cadmium exposure. Expression of such proteins was confirmed by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Bioinformatics tools were applied to propose the functional roles of cadmium-binding protein and its association in cadmium tolerance mechanisms. Results The cadmium-tolerant strain (EC01) and intolerant strain (EC07) with the MICs of 1.6 and 0.4 mM, respectively, were isolated. The whole cell lysate of EC01 exhibited approximately two-fold higher in cadmium binding capability than those of the EC07 and ATCC 13047, possibly by the expression of Cd-binding proteins. Our proteomics analysis revealed the higher expression of DUF326-like domain (a high cysteine-rich protein) of up to 220 fold in the EC01 than that of the EC07. Confirmation of the transcription level of this gene by qRT-PCR revealed a 14-fold induction in the EC01. Regulation of the DUF326-like domain in EC01 was more pronounced to mediate rapid cadmium accumulation (in 6 h) and tolerance than the other resistance mechanisms found in the ATCC 13047 and the EC07 strains. The only one major responsive protein against toxic cadmium found in these three strains belonged to an antioxidative enzyme, namely catalase. The unique proteins found in the ATCC 13047 and EC07 were identified as two groups: (i) ATP synthase subunit alpha, putative hydrolase and superoxide dismutase and (ii) OmpX, protein YciF, OmpC porin, DNA protection during starvation protein, and TrpR binding protein WrbA, respectively. Conclusion All these findings gain insights not only into the molecular mechanisms of cadmium tolerance in EC but also open up a high feasibility to apply the newly discovered DUF326-like domain as cadmium biosorbents for environmental remediation in the future.
Keywords: Enterobacter cloacae; Proteomics; Cadmium stress; DUF326-like domain; Cadmium binding; Cadmium accumulation; Cadmium tolerance; 2D-DIGE; Environment; Bioinformatics